Development and feasibility evaluation of a low cost smart voyage data recorder: marine black box - Abir, Imtiaz Kalam; Rashid, Md. Tahmid; Zaman, Hamid; Hassan, Moontasir; Rafique, Rumana; Rhaman, Md. Khalilur (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 5th IEEE International Conference on Control System, Computing and Engineering, ICCSCE 2015; PARKROYAL Penang ResortBatu Ferringhi, Penang; Malaysia; 27 November 2015 through 29 November 2015 [© 2015 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICCSCE.2015.7482210